Timing and frequency of financial education and positive financial behaviors - Augustin, Lua A. V.; Martin, Terrance K. (Financial Services Review, 2023)
The association between timing and frequency of financial education and financial behaviors has not been studied in tandem. Various studies indicate the more financial education individuals have, the better their chances of making quality financial decisions. In addition to receiving financial edu- cation, the timing and frequency of that education may be relevant to overall decision quality. Early and frequent exposures are expected to have a compounding effect on positive financial behaviors. Using the 2015 wave of the National Financial Capability Study, we found that the timing and fre- quency of financial education are positively associated with positive financial behaviors. This is important because it indicates that the more individuals know about their finances the more likely they are to engage in actions that will have a positive association with their financial futures.